Cholesterol-lowering Action of BNA-based Antisense Oligonucleotides Targeting PCSK9 in Atherogenic Diet-induced Hypercholesterolemic Mice - Tsuyoshi Yamamoto; Mariko Harada-Shiba; Moeka Nakatani; Shunsuke Wada; Hidenori Yasuhara; Keisuke Narukawa; Kiyomi Sasaki; Masa-Aki Shibata; Hidetaka Torigoe; Tetsuji Yamaoka; Takeshi Imanishi; Satoshi Obika (Elsevier, 2012)
Recent findings in molecular biology implicate the involvement of proprotein convertase subtilisin/kexin type 9 (PCSK9) in low-density lipoprotein receptor (LDLR) protein regulation. The cholesterol-lowering potential of anti-PCSK9 antisense oligonucleotides (AONs) modified with bridged nucleic acids (BNA-AONs) including 2',4'-BNA (also called as locked nucleic acid (LNA)) and 2',4'-BNANC chemistries were demonstrated both in vitro and in vivo. An in vitro transfection study revealed that all of the BNA-AONs induce dose-dependent reductions in PCSK9 messenger RNA (mRNA) levels concomitantly with increases in LDLR protein levels. BNA-AONs were administered to atherogenic diet-fed C57BL/6J mice twice weekly for 6 weeks; 2',4'-BNA-AON that targeted murine PCSK9 induced a dose-dependent reduction in hepatic PCSK9 mRNA and LDL cholesterol (LDL-C); the 43% reduction of serum LDL-C was achieved at a dose of 20 mg/kg/injection with only moderate increases in toxicological indicators. In addition, the serum high-density lipoprotein cholesterol (HDL-C) levels increased. These results support antisense inhibition of PCSK9 as a potential therapeutic approach. When compared with 2',4'-BNA-AON, 2',4'-BNANC-AON showed an earlier LDL-C-lowering effect and was more tolerable in mice. Our results validate the optimization of 2',4'-BNANC-based anti-PCSK9 antisense molecules to produce a promising therapeutic agent for the treatment of hypercholesterolemia.